Analysis of possibility of using indicator method to study functional groups of surface of new components of building materials. Issue 1 (March 2020) - Melnikova, A V
Abstract: The current trend to increase the volume of construction of public and industrial facilities the need for new modern building materials is as high as ever. The physicochemical and mechanical properties of the materials obtained are especially important, the improvement of which is often provided by the introduction of new additives into the composition. Using the indicator method to study the surface of new components of building materials can help to assess the impact of the nature of their surface on the final product.